Reliable electrochemical setup for in situ observations with an atmospheric SEM. (11th June 2022) - Yoshida, Kaname; Sasaki, Yuki; Kuwabara, Akihide; Ikuhara, Yuichi
Abstract: A novel setup for the in situ observation of electrochemical reactions in liquids through atmospheric scanning electron microscopy (SEM) is presented. The proposed liquid-phase electrochemical SEM system consists of a working electrode (WE) on an electrochemical chip and other two electrodes inserted into a liquid electrolyte; electrochemical reactions occurring at the WE are controlled precisely with an external potentiostat/galvanostat connected to the three electrodes. Copper deposition from a CuSO4 aqueous solution was conducted onto the WE, and simultaneous acquisition of nanoscale images and reliable electrochemical data was achieved with the proposed setup.